Exploring Issues Regarding Fish Consumption by College Students in Bandung - Nurjaman, Ichsan Muhammad; Aprianingsih, Atik (Journal of Business and Management, 2015)
Abstract. Social marketing campaign is a method of using marketing concept that used by some institutions such as governments and companies with the goals of changing the behavior. Lots of social marketing campaign have been successfully implemented, especially in the health field such as Social HIV prevention campaign, smoke free, diet for health and etc, The first step to construct social marketing campaign is â€œExploring Behavior of Target Audienceâ€. In this research, the researcher will analyze the behavior of the college students towards consumption of fish dishes .The basic problem of this study is the low level of fish consumption of college students in West java , especially Bandung, which is inversely proportional to the high rate of fish production in West Java. The analysis in this study is based on two concepts, first is marketing mix 4P's that used in social marketing campaign and the second is consumer decision making process. Using these two approaches, the researcher can describe the characteristics of college student behavior in consuming fish dishes in Bandung. The reserarch result becomes the recommendation for government program â€œGEMARIKANâ€ as social marketing campaign strategy to increase fish consumption rate of college students in Bandung. The researcher used descriptive analysis in this research, 100 questionnaires had been distributed to college students in Bandung. The scope of the area only focus in Bandung, and the time of execution started from the beginning of June 2015 until the beginning of August 2015. Overall the results are family is the best influencer that affect college students to consume fish dishes, Instagram is a very effective media used in this campaign, and this program needs cooperation with the cafÃ© or restaurant that was always visited by college students. Â Keywords: Social Marketing Campaign, Marketing mix 4P,Consumer decision making rules, College Student, Descriptive Analysis, GEMARIKAN.